Bisphosphonate Use and Cardiovascular Outcomes According to Kidney Function Status in Post-Menopausal Women: An Emulated Target Trial from the Multi-Ethnic Study of Atherosclerosis - Elena Ghotbi; Nikhil Subhas; Michael P. Bancks; Sammy Elmariah; Jonathan L. Halperin; David A. Bluemke; Bryan R Kestenbaum; R. Graham Barr; Wendy S. Post; Matthew Budoff; João A. C. Lima; Shadpour Demehri (Diagnostics, 2025)
Background/Objectives: Bisphosphonates may influence vascular calcification and atheroma formation via farnesyl pyrophosphate synthase inhibition in the mevalonate pathway regulating bone and lipid metabolism. However, the clinical impact of NCB use on cardiovascular outcomes remains uncertain, largely due to methodological heterogeneity in prior studies. We aimed to evaluate the association between nitrogen-containing bisphosphonate (NCB) therapy and coronary artery calcium (CAC) progression, as well as the incidence of cardiovascular disease (CVD) and coronary heart disease (CHD) events. Methods: From 6814 participants in MESA Exam 1, we excluded males (insufficient male NCB users in the MESA cohort), pre-menopausal women, baseline NCB users, and users of hormone replacement therapy, raloxifene, or calcitonin. Among 166 NCB initiators and 1571 non-users with available CAC measurements, propensity score matching was performed using the available components of FRAX, namely age, race, BMI, LDL cholesterol, alcohol, smoking, and steroid use, and baseline CAC yielded 165 NCB initiators matched to 473 non-users (1:3 ratio). Linear mixed-effects models evaluated CAC progression, and Cox models analyzed incident CVD and CHD events. Results: In the overall cohort, NCB use was not significantly associated with CAC progression (annual change: −0.01 log Agatston units; 95% CI: −0.05 to 0.01). However, among participants with a baseline estimated glomerular filtration rate (eGFR) < 65 mL/min/1.73 m2, NCB use was associated with attenuated CAC progression compared with non-users (−0.06 log Agatston units/year; 95% CI: −0.12 to −0.007). No significant association was observed between NCB use and incident CVD events in the overall cohort (HR: 0.90; 95% CI: 0.60−1.36) or within kidney function subgroups. Conclusions: Incident NCB use among postmenopausal women with mild or no CAC at baseline was associated with reduced CAC progression only in women with impaired kidney function. However, this association did not correspond to a decreased risk of subsequent cardiovascular events, suggesting that the observed imaging benefit may not translate into meaningful clinical association.